2015
DOI: 10.1080/15228932.2015.1065620
|View full text |Cite
|
Sign up to set email alerts
|

Offenders’ Crime Narratives Across Different Types of Crimes

Abstract: The current study explores the roles offenders see themselves playing during an offence and their relationship to different crime types. One hundred and twenty incarcerated offenders indicated the narrative roles they acted out whilst committing a specific crime they remembered well. The data were subjected to Smallest Space Analysis (SSA) and four themes were identified: Hero, Professional, Revenger and Victim in line with the recent theoretical framework posited for Narrative Offence Roles . Further analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 20 publications
1
30
0
1
Order By: Relevance
“…The above narrative themes have been identified in a number of previous studies, for a range of different crime types (Canter and Youngs , ; Canter, Kaouri and Ioannou ; Ioannou ; Ioannou et al . ; Youngs and Canter ). The present study aims to examine whether the Narrative Action System (NAS) (Canter and Youngs ) can also be applied to contract killing.…”
Section: Canter and Youngs’ Narrative Action System Model Applied To mentioning
confidence: 99%
“…The above narrative themes have been identified in a number of previous studies, for a range of different crime types (Canter and Youngs , ; Canter, Kaouri and Ioannou ; Ioannou ; Ioannou et al . ; Youngs and Canter ). The present study aims to examine whether the Narrative Action System (NAS) (Canter and Youngs ) can also be applied to contract killing.…”
Section: Canter and Youngs’ Narrative Action System Model Applied To mentioning
confidence: 99%
“…However, it has been reported (Youngs, Ioannou, & Eagles, ) that specialisation is represented through expressive and instrumental offenders, although if this relates to geo‐behaviour remains unclear. It would be useful to examine the criminal narratives of these two groups of offenders as has been successfully applied in other studies (Ioannou, Canter, Youngs, & Synnott, ; Ioannou, Canter, & Youngs, ; Ioannou, Hammond, & Simpson, ; Ioannou, Synnott, Lowe, & Tzani‐Pepelasi, ; Ioannou, Synnott, Reynolds, & Pearson, ; Yaneva, Ioannou, Hammond, & Synnott, ). This would be in respect to their geographic profiles to ascertain if the lack of variation is geographic behaviour is consistent in their offender narrative.…”
Section: Discussionmentioning
confidence: 99%
“…If they are; then these items would be represented in similar regions and would provide evidence for distinct criminal narrative experiences in PD and psychopathic offenders. A number of studies from have found such MDS models to be productive in recent years (Ioannou, Canter, Youngs & Synnott 2015;Ioannou, Hammond & Simpson, 2015;Youngs, Ioannou & Eagles, 2016;Ioannou, Canter & Youngs, 2017;Ioannou, Synnott, Lowe & Tzani-Pepelasi, 2018;Yaneva, Ioannou, Hammond & Synnott, 2018, Synnott, Ioannou, Coyne & Hemingway, 2018).…”
Section: Discussionmentioning
confidence: 99%